(untitled) (Journal of actual problems of jurisprudence, 2018)
Building the rule of law is not possible without the formation of a developed legal culture. In this article, the legal culture is seen as an indicator of the quality of the legal life of society, as the level of development of legal activities, legal acts of justice and the rule of entities and society as a whole. The article reveals the peculiarities of the legal culture of judges. It is emphasized that the legal culture of judges is not reducible only to legal literacy and understanding of legal dogma. The basis of the legal culture is humane, moral and spiritual in general, began. Without them, the social role of legal awareness and legal culture can not be significant. The author emphasizes that it is important for the judge to maintain the balance between humanity (kindness) and severity (fair). Legal culture is closely linked with the judge his moral character. Here, the primary role played by the awareness of his duty by the judge, his beliefs, and self-education. This task is both personal and public. Key words: judge, legal culture, legal, legal mentality, legal nihilism, justice, duty, moral qualities.